2013
DOI: 10.1007/s00404-013-2853-5
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic pre-operative bilateral ureteric catheters for major gynaecological surgery

Abstract: Prophylactic pre-operative ureteric catheters are quick and easy to insert and associated with low complication rates. Routine use before major gynaecological surgery can expedite intra-operative identification of the ureters and may reduce accidental ureteric injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…Others do not find any clear benefit of using ureteric catheters. 13 In our study 23.4% ureteric injury patients had prophylactic ureteric catheterization. Injury forms were complete transection in 61%; ligation in 7%; partial transection in 3% and excision in 29%.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Others do not find any clear benefit of using ureteric catheters. 13 In our study 23.4% ureteric injury patients had prophylactic ureteric catheterization. Injury forms were complete transection in 61%; ligation in 7%; partial transection in 3% and excision in 29%.…”
Section: Discussionmentioning
confidence: 61%
“…Postoperative complications involving the urinary tract which included urinary tract infection (UTI) (5/337 patients, 1.48 %), acute renal failure (2/337, 0.6%), and ureterovaginal fistulae (1/337 patients, 0.3%) 6% ureteral stricture after ureteroneocystostomy. 13 Selzman et al reported that ureterovaginal fistulas resolved in all seven patients treated with an internal ureteral stent. 1 Tanagho et al found that after persistent reflux, five patients experienced progressive renal deterioration.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Urologic injuries can be prevented by thoroughly identifying the ureter and careful surgical technique avoiding excessive devascularization of the ureter and excessive use of the cautery. The use of prophylactic stents in conventional laparoscopy and laparotomy has not shown to be cost effective for the prevention of urologic injury and has not been studied in robotic-assisted gynecologic surgery [77,78]. Bowel and vascular injuries have a low incidence and similar causes than conventional laparoscopic surgery.…”
Section: Surgical Complicationsmentioning
confidence: 99%
“…There are a few reports on the efficacy of ureteral stent placement (USP) in total hysterectomy and laparoscopic surgery for benign diseases 1,4 . However, there are only a few reports on the efficacy of USP in cases of malignant tumors, and the few available reports are centered on only one type of gynecological cancer or include a small number of cases 5 . To our knowledge, there are no reports on the efficacy of USP in several gynecological cancers, including cervical, uterine, and ovarian cancers.…”
Section: Introductionmentioning
confidence: 99%